Effect of Plyometric Training on Electromyographic Activity of Hip Abductor and Adductor Muscles in Women With Ligament Dominance: A Randomized Clinical Trial - Farzaneh Ramezani; Farzaneh Saki; Behdad Tahayori (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Anterior Cruciate Ligament (ACL) injury is one of the most common non-contact lower extremity injuries among athletes. Ligament dominance is considered as one of the modifiable factors of ACL injury. This study aimed to evaluate the effect of plyometric training on electromyographic activity of hip abductor and adductor muscles in women with ligament dominance. Methods: This is a randomized clinical trial conducted on 24 female athletes with ligament dominance, (Dynamic knee valgus angle >12 degrees), who were purposefully selected and randomly divided into two groups of training (n=12) and control (n=12). The training group performed plyometric training with verbal feedback for eight weeks, while the control group performed their regular training. The feedforward and feedback activity of hip abductor (gluteus maximus, gluteus medius, and tensor fascia latae) and adductor muscles (adductor longus) were assessed during a single-leg countermovement jump task 100 milliseconds before and after foot-ground contact. Paired t-test and multivariate covariance analysis were used to analyze the collected data. The significance level was set at 0.05. Results: A significant increase in gluteal muscles activity and a decrease in adductor longus muscle activity was reported in the training group (P<0.05), but not in the control group (P>0.05). In comparing the mean scores of the two study groups, a significant difference was observed in gluteal muscles' feedforward activity (P<0.05). Conclusion: Eight weeks of plyometric training with verbal feedback can improve the electromagnetic activity of hip abductor and adductor muscles in women with ligament dominance and thus reduce the risk of ACL injury.